Relationship between Secular Trends of Prevalence Rate and Detection Rate of New Cases of Leprosy in Thailand during the 14 years Post Elimination of Leprosy (1994 - 2007) - รามสูต ธีระ; รุ่งตระกูลชัย สมชาย; เสร็จกิจ ฉลวย (Disease Control Journal, 2009)
The author has conducted an epidemiological study on the secular trends and relationship between prevalence rate and detection rate of new leprosy cases in Thailand during the last 14 years post elimination of leprosy (1994-2007). This study also attempted to compare between using two statistical models for such trend analysis namely the quadratic trend model and the linear trend model and found that the latter was better in terms of appropriateness and accuracy. Overall results revealed irregular decreasing trends of both indicators at the beginning years while became more regularly decreasing during later years. However, corresponding trends were found among such two rates with positive statistically significant coefficient (r = 0.79, p-value = 0.001). Prevalence rate was decreasing 80.46 percent from 0.84 per 10,000 population in 1994 to 0.17 per 10,000 population in 2007 with annual decreasing rate of 5.75 percent. Meanwhile 60 percent decreasing rate of detection rate of new cases from 0.20 per 10,000 population in 1997 to 0.18 per 10,000 population with annual decreasing rate of 4.28 percent were observed. By application of the linear trend model to forecast future trends, it was found that prevalence rate from 2008 -2011 will be 0.09, 0.06, 0.02, and 0 per 10,000 population respectively while detection rate of new cases will be 0.06, 0.05, 0.04 and 0.03 per 10,000 population respectively. In addition, the author has made comparison on decreasing trends of such two indicators before and after successful elimination of leprosy since beginning of MDT implementation, together with discussion on influence and impact of relating operational variables on such current trends and future trends. More emphasis was made on impacts of the new policy of the universal health insurance which increased opportunities and access to diagnosis and MDT coverage to people, together with attempt towards hospital accreditation, leprosy elimination accreditation, and health promotion hospital accreditation for reorientation and quality improvement of the health service system. All of these developments were key successful factors for current and future progress and success of sustainable leprosy elimination.